Evaluation of the Incorporation of Waste Generated from Titanium Dioxide Manufacturing in Red Ceramics - Ribeiro, Daniel Veras; Figueiredo, Samia Cordeiro; Machado, Alexandre Teixeira; Valenzuela Diaz, Francisco Rolando [UNESP]; Caldas Souza, Carlos Alberto (Univ Fed Sao Carlos, Dept Engenharia Materials, 2015)
Rotary-vacuum-filter mud (RVFM) is waste generated during the manufacturing process of titanium dioxide. In this work, RVFM and ceramic bricks containing different ratios of this waste are investigated. The mud samples were characterized using thermal analysis (TG/DTG). The aim of the present work was to determine the effect of adding RVFM on the ceramic properties of clay, such as apparent porosity, water absorption, linear shrinkage and flexural strength, used to produce red ceramics (bricks and roofing tiles). Samples were dried out at 110 degrees C and fired at 800 degrees C, 950 degrees C and 1100 degrees C. The addition of RVFM tends to increase the apparent porosity and water absorption and to decrease the flexural strength of the ceramic specimens. Based on the results, ceramic specimens with 20% RVFM content that are burned at 800 degrees C can not be used as bricks, and ceramic specimens with 20% RVFM content that are fired at 800 degrees C and 950 degrees C can not used as roofing tiles, according to Brazilian standards.
Keywords: waste recycling; mud (RVFM); titanium dioxide; red ceramic